Evaluation of The Implementation of The Social and Environmental Responsibility Angkasa Pura I: a Study of Care for Disabilities Program - Faustina Rahmasarita; Ni Komang Septia Noriska (PT FORMOSA CENDEKIA GLOBAL, 2023)
Corporate social responsibility (CSR) is a company’s commitment to society and the environment. The aim of this study is to determine the process of implementing the The Social and Environmental Responsibility Angkasa Pura I Care for Disabilities program on the CSR of PT Angkasa Pura I Adi Soemarmo International Airport and the impact felt by the community. This study is a qualitative descriptive study in which the researchers analyzed, described, and summarized various conditions and situations from various data collected in the form of observations, direct interviews with Adi Soemarmo Airport CSR Officers and Principals as recipients of Adi Soemarmo Airport CSR assistance funds, and documentation. The target of this program was three special schools (SLB) located nearby the company, with a maximum fund distribution of IDR 10,000,000 per SLB. From this study, it can be inferred that PT Angkasa Pura I Adi Soemarmo Airport has implemented CSR as stipulated in the law and government regulations